A Case Report on Hyperlipidemia in a Child - Rahman, Sajjad Ur; Ul Wadood, Atta; Muhammad Aitzaz; Jan, Rafi Ullah; Shafi Ullah; Jan, Muhammad Wajahat; Waleed, Muhammad (Journal of Postgraduate Medical Institute, 2025)
Hyperlipidemia in pediatric age group is usually due to genetic disorders of lipid metabolism. Familial hypercholesterolemia is a classic example of genetic hyperlipidemia which results in premature atherosclerotic diseases. We present a case of 5 years old child with familial hypercholesterolemia evident by high cholesterol and LDL-C levels which responded to statins without causing any significant adverse effects. Besides statins other therapies can also be incorporated for lipid lowering like adding ezitimibe, PCSK-9 inhibitors and rarely used treatment modality called lipoprotein apheresis. Familial Hypercholestermia is a disorder which needs early diagnosis and initiation of prompt treatment in order to prevent early onset atherosclerosis and its complications. This case report is being published for its rarity and early diagnosing and management.